Innovate, invest, commercialize: Advancing Africa’s reproductive health - Friday Okonofua; Lorretta Favour Chizomam Ntoimo (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
Africa cannot achieve universal health coverage, gender equality, or sustainable development while millions of women, adolescents, and couples continue to experience preventable sexual and reproductive health and rights (SRHR) problems. The continent has made important progress, but the pace is far too slow. In 2023, sub-Saharan Africa accounted for approximately 70% of global maternal deaths, with about 182,000 women dying from pregnancy-related causes. Although maternal mortality in the region fell by 40% between 2000 and 2023, Africa would need a dramatic acceleration in the annual rate of decline to achieve the Sustainable Development Goal target by 2030